A Population-Based Study on the Association between Statin Use and Sudden Sensorineural Hearing Loss. (February 2015) - Chung, Shiu-Dong; Chen, Chao-Hung; Hung, Shih-Han; Lin, Herng-Ching; Wang, Li-Hsuan
Objectives: No study has reported the relationship between statin use and sudden sensorineural hearing loss (SSNHL). In this study, we examined the association between statin use and SSNHL using a population-based dataset. Study Design: A case-control study. Setting: Taiwan. Subjects and Methods: The study sample was selected from the Taiwan Longitudinal Health Insurance Database. We identified 1263 subjects aged ≥40 years with SSNHL and 6315 sex-, age-, hypertension-, and coronary heart disease–matched controls. We used conditional logistic regression to compute the odds ratio (OR) for having been a previous statin user between cases and controls. Furthermore, we performed conditional logistic regression to explore the relationship of regular and irregular statin users with SSNHL. Results: There was a significant difference in the prevalence of statin use between cases and controls (27.2% vs 21.3%, respectively; P < .001). The OR of statin use before the index date for cases was 1.36 (95% confidence interval [CI], 1.18-1.57) compared to controls after taking gender, age group, hypertension, coronary heart disease, diabetes, renal disease, and hyperlipidemia into consideration. Furthermore, compared to controls, the adjusted ORs of regular and irregular statin use for cases were 1.30 (95% CI, 1.11-1.52) and 1.49 (95% CI, 1.11-1.93), respectively, compared to controls. Conclusion: This study found that SSNHL was significantly associated with previous statin use.